The Effect of Anacardium Occidentale Leaves Extract with Various Concentrations Used as Denture Cleanser on Streptococcus Mutans Growth - Kristiana, Dewi (The Indonesian Journal of Dental Research)
Introduction: Microbial adhesion on dentures surface can cause proliferation on bacteria colony, leads to formation of plaque which induce bad smell in mouth and denture stomatitis. There is evidence about denture stomatitis caused by another biofilm species, Streptococcus mutans (S. mutans). This study was aimed to observe efficacy differences on S. mutans growth inhibition of Anacardium occidentale leaves extract between various concentrations of 25%, 50%, and 75% as denture cleanser after 45 min immersing. Materials and methods: Samples were made from heat-cured resin acrylic plates with dimension of 10 x 10 x 1 mm. Heat-cured resin acrylic plates were immersed in Anacardium occidentale leaves extract with concentration of 25%, 50%, and 75% for 45 minutes. Each concentration contained of 8 samples. In control group, heat-cured resin acrylic plates were immersed in distilled water. To observe inhibiting effect of Anacardium occidentale leaves extract on S. mutans growth,spectrophotometer was used. Data were analyzed using one way ANOVA and LSD test. Results: Data analyses using one way ANOVA showed significant differences (p<0.05). In LSD test, significant differences on S. mutans growth inhibition effect of Anacardium occidentale leaves extract between concentration 25%, 50%, and 75% after immersing heat-cured resin acrylic plates for 45 minutes was found. Conclusion: In conclusion, Anacardium occidentale leaves extract in concentration of 75% used to immerse the acrylic plate for 45 minutes effectively inhibited the growth of S. mutans.